No Load Behavior Prediction of Large Five-Legged Transformers Using Topological Transient Models - Zirka, Sergey; Albert, Dennis; Fröhlich, Alexander (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The work proposes a method of reproducing the no-load losses and currents of large five-legged transformers with the use of their transient models. This aim is achieved by employing topological transformer models based on a dynamic hysteresis model (DHM) and taking into account equivalent transformer capacitances. It is proposed to reproduce initially the measured total losses by using DHM means, and then to determine an equivalent per phase capacitance value that provides a best possible coincidence of calculated and measured current waveforms.